Analisis Pengaruh Non Performing Loan, Dana Pihak Ketiga Terhadap Profitabilitas Dengan Loan To Deposit Ratio Sebagai Variabel Moderasi - Putra Anugrah Dimas Januardhy (International Forum of Researchers and Lecturers, 2023)
This study aims to examine the effect of Non Performing Loans and Third Party Funds on Profitability and to examine the effect of Non Performing Loans and Third Party Funds with Loan To Deposit Ratio as a Moderating Variable in Conventional General Banking Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The research method used in this research is quantitative research. The sample in this study was selected using a purposive sampling method and a sample of 41 banking companies that met the sample criteria was obtained. The data analysis method used is simple linear regression analysis and moderate regression analysis. The results of this study indicate that Non-Performing Loans and Third Party Funds have no effect on Profitability. In moderation the Loan To Deposit Ratio strengthens the effect of Non Performing Loans and Third Party Funds on Profitability.